Vitamin D Status Among Patients With Dry Eye Syndrome Attended In Bangabandhu Sheikh Mujib Medical University (BSMMU) (The Journal of Ad-din Women's Medical College, 2023)
Background: Dry eye syndrome (DES) is a common ocular manifestation. Artificial tears provide relief of eye irritation in patients with aqueous tear deficiency, but do not treat the underlying inflammation in Dry eye syndrome. Aim: To assess the vitamin D status of the dry eye syndrome patients.Methodology: This cross-sectional study was conducted in the Department of Community Ophthalmology, BSMMU, Shahbag, Dhaka, from July 2019 to June 2020. Within the period a total of 50 cases of dry eye syndrome patients that met the inclusion criteria were taken as samples after receiving their informed consent. Detailed history, physical examination and Ophthalmological examination including Tear film Breakup Time (TBUT) of each patient was performed and recorded. Eye discomfort was assessed by the Ocular Surface Disease Index (OSDI) the score of which ranges from 0 to 100. A score of 12 was used as a cutoff for normal, 13–22 for mild dry eye, 23–32 for moderate dry eye, and ≥ 33 for severe dry eye. Tear film Breakup Time (TBUT)